Efektivitas Pendekatan Kontekstual dan Bercerita dalam Meningkatkan Kemampuan Literasi Anak Jalanan di Kota Tasikmalaya - Herawati, Herfina; Jilda Permata Nur Aliya; Eva Siti Ridiyanti; Nida Nurul Padilah; Mita Puspita Sari; Rika Yunita; Lesi Oktiwanti (Universitas Muhammadiyah Magelang, 2026)
Street children are a vulnerable group often facing barriers to formal education due to economic, social, and administrative factors, resulting in low basic literacy skills. This study aims to analyze the validity of a non-formal learning model and examine the effectiveness of the Contextual Teaching and Learning (CTL) approach combined with storytelling methods in improving the basic literacy skills of street children. This study employed a quantitative approach with a one-group pretest-posttest design. The subjects consisted of six street children in Cipedes District, Tasikmalaya City, selected through purposive sampling. The research instruments were validated by four expert lecturers using Aiken’s V index, while literacy data were collected through objective tests administered before and after the intervention. Data analysis was performed using descriptive statistics and the Wilcoxon Signed-Rank test. The results indicated that the learning model had a high level of content validity, with an average Aiken’s V index of 0.94. There was a significant improvement in participants' literacy skills, evidenced by an increase in the mean score from 66.83 in the pretest to 81.67 in the post-test, with an N-Gain of 14.83. The Wilcoxon test yielded a Z-value of -2.20 (p < 0.05), confirming a significant difference between pre and post intervention scores. All participants (100%) demonstrated improved abilities. It is concluded that integrating the contextual approach and storytelling is an effective non-formal learning strategy for enhancing the basic literacy of street children.